CONFIDENCE SHOCKS IN EMERGING MARKETS AND THEIR GLOBAL CONTAGION: INSIGHTS FROM G-CUBED SIMULATIONS - Sofa, Wahyuni Andriana; Wahyuni, Ribut Nurul Tri; Kartiasih, Fitri (Universitas Gunadarma, 2025)
The global economy has begun to recover from the global financial crisis (GFC), which occurred around 10 years ago, according to recent economic statistics. However, investor confidence has declined in a number of significant emerging markets (EMEs) due to rising interest rates in the US and ongoing trade tensions between the US and China, potentially causing contagion effects worldwide. The worldwide impacts of the financial crisis in certain important EMEs, namely Argentina, Brazil, Turkey, and Russia (ABTR), as well as its widespread impact on raising global investment and consumption risk, are examined in this paper using the G-Cubed model for G-20 nations with six sectors. According to the findings, because three distinct shocks struck at the same time in ABTR countries—where the initial shock emerged—they experience the most negative short-term effects of the confidence crisis. The cost of capital rises as a result of the capital outflow from these nations, which causes firms to disinvest or reduce their capital stock. Households across all nations are also more likely to discount future income streams as a result of their increased risk assessment, which promotes more savings and lower spending. Additionally, both developed and non-shocked emerging countries grew as a result of increased capital inflows, but their trade balances worsened due to exchange rate appreciation, which made the production decline worse.